2022
DOI: 10.1590/fst.53121
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of microcytic hypochromic anemia with red blood cell survival via carbon monoxide breath-red blood cell survival

Abstract: Cr to determine blood volume and RBCS) (Gray & Sterling, 1950;Ebaugh et al., 1953). Although this method has been used as the gold standard, it takes weeks to measure RBCS, and it is not safe to use in infants and pregnant woman. Recently, a rapid and noninvasive carbon monoxide (CO) breath test has been developed to determine RBCS (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…ELS showed the opposite pattern, being shortest in patients with TI, followed by HbH-CS, TM, and MIX, and longest in del-HbH disease. Li et al 10 reported that the ELS values in patients with mild β-thalassemia and severe α/β thalassemia were 67.5 days and 30.2 days, respectively, but did not provide definitions of severe and mild β-thalassemia or clarify the type of α-thalassemia. HbH disease can be classified as deletional or non-deletional based on genotype.…”
Section: Discussionmentioning
confidence: 99%
“…ELS showed the opposite pattern, being shortest in patients with TI, followed by HbH-CS, TM, and MIX, and longest in del-HbH disease. Li et al 10 reported that the ELS values in patients with mild β-thalassemia and severe α/β thalassemia were 67.5 days and 30.2 days, respectively, but did not provide definitions of severe and mild β-thalassemia or clarify the type of α-thalassemia. HbH disease can be classified as deletional or non-deletional based on genotype.…”
Section: Discussionmentioning
confidence: 99%